Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T19:10:46+01:00
A) (3-2x)+(3x+4)= -(3-2x)+(5x+4)
3-2x+3x+4= -3+2x+5x+4
-2x+3x-2x-5x= -3+4-3-4
-6x=-6 /:(-6)
x=1
b) -(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x-2x+2x=-3+1+8+3
-3x=9 /:(-3)
x=-3
2010-03-03T19:11:24+01:00
A) 3-2x+3x+4= -3 + 2x +5x +4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6/:(-6)
x=1
b)-x-3-2x-8=-3+2x+2x+1
-x-2x-2x-2x=-3+1+3+8
-7x=7/:(-7)
x= - 1
2010-03-03T19:12:39+01:00
A) (3-2x)+(3x+4)= -(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
7+x=1+7x
6=6x
x=1

b) -(x+3)-(2x+8)=(-3-2x)+(2x+1)
-3x-11=-2
-3x=9
x=-3

Pozdrawiam w razie pytań pisać ! :)